Sea Water Desalination in Microgrids - Rosales-Asensio, Enrique; García-Moya, Francisco José; Borge-Diez, David; Colmenar-Santos, Antonio (Green Energy and Technology, 2022)
XXII, 221 p. 111 illus., 103 illus. in color.